The world of animals - Leach, Michael; e (London : Arcturus, 2022)
This exciting and eye-opening hardback takes young readers on a journey of discovery through the animal kingdom. The chapters are divided by continent with annotated, full-color maps, demonstrating the extraordinary variety of our planet's animals - and showcasing many creatures that will be unfamiliar to many young readers.
Animal planet -- What is that animal? -- Africa -- North America -- South America -- Asia -- Europe -- Oceania -- Animals under threat -- People and animals -- How to help animals and the planet.
3-6
Includes index.
An illustrated guide to the wonders of the wild.
Keywords: Animals -- Juvenile literature